Inhibition of the NLRP3 inflammasome limits the inflammatory injury following myocardial ischemia–reperfusion in the mouse. (15th April 2016) - Toldo, Stefano; Marchetti, Carlo; Mauro, Adolfo G.; Chojnacki, Jeremy; Mezzaroma, Eleonora; Carbone, Salvatore; Zhang, Shijun; Van Tassell, Benjamin; Salloum, Fadi N.; Abbate, Antonio
Abstract: Background: Successful reperfusion is the most effective strategy to reduce ischemic injury in acute myocardial infarction (AMI). Ischemic injury, however, also triggers a secondary ischemia–independent injury, known as reperfusion injury, contributing to the overall infarct size. We hypothesize that inhibition of the Nod-like Receptor Protein-3 (NLRP3) inflammasome limits infarct size following myocardial ischemia/reperfusion (I/R), by inhibiting the inflammatory component of the reperfusion injury. Methods: CD-1 male mice underwent transient ligation of the left anterior descending coronary artery for 30 or 75 min followed by reperfusion. Infarct size was measured at 1, 3 and 24 h. A NLRP3 inflammasome inhibitor (NLRP3inh) or vehicle was administrated immediately at time of reperfusion or with a delay of 1 or 3 h of reperfusion. Results: A time-dependent increase in infarct size was measured at 1, 3, and 24 h after reperfusion (11 ± 2%, 30 ± 5% and 43 ± 4% of the area at risk respectively; P < 0.001 for trend). NLRP3 myocardial expression was significantly increased at 24 h and 6 h vs 3 h (P < 0.01). Administration of the NLRP3inh at reperfusion did not reduce infarct size at 3 h, while it significantly reduced infarct size at 24 h (− 56% vs vehicle, P < 0.01). The NLRP3inh given 1 h after reperfusion also significantly decreased caspase-1 activity and infarct size measured at 24 h, whereas the NLRP3inh did not when given with a delay of 3 h. Conclusions: Pharmacological inhibition of the NLRP3 inflammasome within 1 h of reperfusion limits the secondary inflammatory injury and infarct size following myocardial ischemia–reperfusion in the mouse.